Citizenship Status and Arrest Patterns for Violent and Narcotic-Related Offenses in Federal Judicial Districts along the U.S./Mexico Border - Sibila, Deborah (American journal of criminal justice, 2017)
Media reports routinely reference the drug-related violence in Mexico, linking crime in communities along the Southwest U.S. Border to illegal immigrants. The primary purpose of the current research is to examine whether the media assertions can be supported. Logistic regression models were run to determine the impact of citizenship on the likelihood of disproportionate arrest for federal drug and violent crimes, along the U.S./Mexico border. In arrests for homicide, assault, robbery, and weapons offenses, U.S. citizens were disproportionately more likely than non-citizens to be arrested. The only federal crime where non-citizens were disproportionately more likely to be arrested than were U.S. citizens was for marijuana offenses. Results of the current study challenge the myth of the criminal immigrant.